AKTIVITAS BISNIS PERSPEKTIF ISLAM DAN KAPITALIS (Analisa Komparatif Terhadap Aspek Fundamental Ekonomi Islam dan Kapitalis dalam Aktivitas Bisnis) - Rosyidin Rosyidin (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Problems of primal which it is important to know, psychologyly that human being character is not will have left nothing to be desired with a[n certain matter. Although in its life have full by properties estae which abundance. Because theoretically said that:, Earnings excelsior, hence excelsior also assess utilitas to reach. Not surprise if later; then a lot place economics as solution fundamental, problem faced of human being, minimum its bearing which often occupy dominant position. Human being claimed to can to conduct the effort exsploration is no desisting in way of solution of problems of economics. And one of source of which cannot be disregarded in problem of economics is Religion. But Islamic economic activity, beside follow economics methods in general, also drape x’self to values of transenden having the character of doctrinal, namely through actualitation conception religion humanism and principal application of consistent islamic in freon configuraton of al-Maqasid asy-Syari’ah